Pengembangan Buku Ajar IPA Kelas VI untuk Siswa Sekolah Dasar - Anita Hidayati; Rufi'i Rufi'i; Yoso Wiyarno (JEMS: Jurnal Edukasi Matematika dan Sains, 2020)
The purpose of this research was to develop a coursebook that can be used to support the activities of Science learning of the first semester at Grade 6 of SDN Sambungrejo Sukodono This Research & Development intended for a learning resource. The research used the development model of Dick and Carey. The subjects of research trials were 50 students and a teacher at the school. The instruments for data collection utilized were the interview, the sheet of expert validation for lecturers and practitioners of education, assessment from expert lecturers, school superintendent, principal, classroom teacher and students. The research results revealed that the eligibility level of the science coursebook based on each aspect of the assessment including feasibility aspects of content obtained an average score 4.086 as "good" category with the level of appropriateness of 81.7%; feasibility aspect of presentation gets an average score of 4.307 as "very good" category with 86.1% eligibility level; on the feasibility of the language, earning an average score of 4.388 "very good" category with the level of appropriateness of 87.75%; While on the graphic aspects it obtained an average score 4.302 as "very good" category with the level of appropriateness of 86%. To conclude, the science coursebook for the first semester and the sixth grade students overall gained an average score 4.271 with "good" category and level eligibility 85.54%. Thus, this book stated feasibility.